2012
DOI: 10.1186/1479-5876-10-58
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of countering neurological impairment by intravenous administration of autologous cord blood in cerebral palsy

Abstract: BackgroundsWe conducted a pilot study of the infusion of intravenous autologous cord blood (CB) in children with cerebral palsy (CP) to assess the safety and feasibility of the procedure as well as its potential efficacy in countering neurological impairment.MethodsPatients diagnosed with CP were enrolled in this study if their parents had elected to bank their CB at birth. Cryopreserved CB units were thawed and infused intravenously over 10~20 minutes. We assessed potential efficacy over 6 months by brain mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 27 publications
(30 reference statements)
0
41
0
Order By: Relevance
“…Increasing use of preimplantation genetic diagnosis (PGD) with HLA matching in Thalassemia endemic regions as South East Asia will see the rise of subsequent related allogeneic cord blood stem cell transplantation both in Thalassemia [9] but also other hereditary conditions [8,9]. Increasing favourable evidence for the potential of autologous UCB in cerebral palsy [10][11][12][13], traumatic and/ or hypoxic brain injury [14,15], diabetes [6,7] and deafness [6,7] may influence UCB banking [16,17]. Hepatitis B virus (HBV) infection remains a major global public health problem, despite the availability of a highly effective vaccine and improvements in antiviral therapy [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing use of preimplantation genetic diagnosis (PGD) with HLA matching in Thalassemia endemic regions as South East Asia will see the rise of subsequent related allogeneic cord blood stem cell transplantation both in Thalassemia [9] but also other hereditary conditions [8,9]. Increasing favourable evidence for the potential of autologous UCB in cerebral palsy [10][11][12][13], traumatic and/ or hypoxic brain injury [14,15], diabetes [6,7] and deafness [6,7] may influence UCB banking [16,17]. Hepatitis B virus (HBV) infection remains a major global public health problem, despite the availability of a highly effective vaccine and improvements in antiviral therapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in view of the recent evidence of UCB's HSC plasticity and the strong evidence supporting the concept that HSCs are pluripotent and the source for the majority, if not all, of the cell types in our body [5], autologous and related allogeneic UCB stem cell storage offers an opportunity for many families for use in future regenerative medical purposes [6,7]. Increasing use of preimplantation genetic diagnosis (PGD) with HLA matching and subsequent related allogeneic cord blood HSCT in Thalassemia [8,9], endemic in South East Asia, and other hereditary conditions [8] and along with favourable support for autologous UCB use in cerebral palsy [10,11,12,13], traumatic and/or hypoxic brain injury [14,15], diabetes [6,7], and deafness [6,7] has already started transforming the field of UCB banking.…”
Section: Introductionmentioning
confidence: 99%
“…Given this background, my colleagues have obtained positive results for the infusion of intravenous autologous CB-MNCs in children with CP in terms of the safety and feasibility of the procedure, as well as its potential efficacy in countering neurological impairment [37]. Another group also recently reported that intravenous infusion of allogeneic CB-MNCs has therapeutic potential in CP [38].…”
Section: Intravenous Infusion Of Mncs For Cell Therapymentioning
confidence: 99%
“…Activated microglial cells could then release neurotrophic factors such as BDNF and glial cell-derived neurotrophic factor (GDNF), remove synapses from damaged neurons and influence the synaptic connectivity of newly-formed neurons [36]. I have also emphasized the importance of the neurotrophic effects of the CBMNCs for improving neurologic outcomes, because most of the patients that responded showed clinical changes within 1 month after CB-MNC infusion [37], and many reports have demonstrated that CBMNCs consistently express neurotrophic factors such as nerotrophin (NT)-5, NT-3, BDNF, and other growth factors [33].…”
Section: Intravenous Infusion Of Mncs For Cell Therapymentioning
confidence: 99%
“…It was also at this time that embryonic stem cells were discovered and characterized by investigators at the University of Wisconsin, 10 who hypothesized that these stem cells might be used to treat a gamut of diseases by using them in cellular therapies, giving rise to the fields of tissue engineering and regenerative medicine. It was not long before investigators at Duke University and elsewhere 11,12 investigated whether HSCs might be used for these types of clinical applications. Based on the ease and costs of procurement, CB-derived HSCs were one of the first stem cell sources that were analyzed.…”
Section: Introductionmentioning
confidence: 99%